2021
DOI: 10.1007/s13562-021-00722-9
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomics reveals differences between commercial and non-commercial Camellia sinensis cultivars used in black tea production

Abstract: Tea (Camellia sinensis) has enthralled both consumers and researchers, and its popularity has increased, due to its taste, aroma and its medicinal attributes, owed largely to its metabolites.The catechins and theaflavins in green and black tea, respectively, have been documented to possess anti-oxidant, anti-inflammatory, anti-cancer, as well as cardiovascular diseasepreventing properties. Tea consumers concern themselves with the quality of tea, in particular, its taste and aroma based on which consumers are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…The method for metabolite extraction determined the quality of results. Organic solvents such as methanol, ethanol and acetonitrile are mainly used as the extraction solvents (Nyarukowa et al ., 2021; Li et al ., 2022c). Applying these solvents with new technologies such as headspace solid‐phase microextraction (HS‐SPME), ultrasound extraction, membrane separation technology and supercritical fluid extraction is more efficient and accurate compared with traditional solid–liquid and liquid–liquid extraction (Cai et al ., 2021).…”
Section: Metabolomics and Tea Key Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The method for metabolite extraction determined the quality of results. Organic solvents such as methanol, ethanol and acetonitrile are mainly used as the extraction solvents (Nyarukowa et al ., 2021; Li et al ., 2022c). Applying these solvents with new technologies such as headspace solid‐phase microextraction (HS‐SPME), ultrasound extraction, membrane separation technology and supercritical fluid extraction is more efficient and accurate compared with traditional solid–liquid and liquid–liquid extraction (Cai et al ., 2021).…”
Section: Metabolomics and Tea Key Metabolitesmentioning
confidence: 99%
“…Theaflavins produced by catechin oxidation is an important colouring substance in fermented tea, which provides freshness, astringency and other flavours (Zhang et al ., 2020). Meanwhile, researchers confirmed that tea types containing high catechin content such as GW Ejulu are more suitable for making fermented tea through metabolomic analysis (Nyarukowa et al ., 2021). It is helpful to improve the quality of fermented tea by optimising the process and increasing the content of theaflavins.…”
Section: Metabolomics and Tea Key Metabolitesmentioning
confidence: 99%